Green Design of Novel Metal Matrix Composites. (February 2019) - Singh, R; Singh, N; Farina, I; Mascolo, I; De Piano, M; Amendola, A; Fraternali, F
Abstract: In the present research work investigations have been made for surface hardness of Al-SiC metal matrix composite (MMC) prepared by combining fused deposition modelling (FDM), vacuum moulding(VM) and stir casting process. This combination resulted into novel method for preparation of MMC as green process in single step with significant reduction in time. The input process parameters (namely:SiC particle size, proportion of SiC, vacuum pressure and VM sand grin size) were studied at three levels using Taguchi L9 orthogonal array to find out there effect on surface hardness of casted specimens. Microstructure analysis was conducted to support hardness data.